Iron in intracellular infection: to provide or to deprive? - Silva-Gomes, Sandro; Vale-Costa, Silvia; Appelberg, Rui; Gomes, Maria Salomé (Frontiers in Cellular and Infection Microbiology, 2013)
Due to their chemical versatility, transition metals were incorporated as cofactors for several basic metabolic pathways in living organisms. This same characteristic makes them potentially harmful, since they can be engaged in deleterious reactions like Fenton chemistry. As such, organisms have evolved highly specialized mechanisms to supply their own metal needs while keeping their toxic potential in check. This dual character comes into play in host-pathogen interactions, given that the host can either deprive the pathogen of these key nutrients or exploit them to induce toxicity toward the invading agent. Iron stands as the prototypic example of how a metal can be used to limit the growth of pathogens by nutrient deprivation, a mechanism widely studied in Mycobacterium infections. However, the host can also take advantage of iron-induced toxicity to control pathogen proliferation, as observed in infections caused by Leishmania. Whether we may harness either of the two pathways for therapeutical purposes is still ill-defined. In this review, we discuss how modulation of the host iron availability impacts the course of infections, focusing on those caused by two relevant intracellular pathogens, Mycobacterium and Leishmania.